145k views
0 votes
If ( 4x - 2 ) ( x + 9 ) - 3x = ax2 + bx + c, what is the value of b. The 2 is and exponent please help me 

2 Answers

3 votes

Answer:

b = -34

Explanation:

Use " ^ " to indicate exponentiation:

( 4x - 2 ) ( x + 9 ) - 3x = ax^2 + bx + c

Perform the indicated multiplication:

4x^2 + 36x - 2x - 18 - 3x becomes

4x^2 - 34x - 18 so b = -34

User JTeagle
by
4.8k points
4 votes

Answer:

b=31 in
ax^2+bx+c

Explanation:

Hi there!


( 4x - 2 ) ( x + 9 ) - 3x

Our goal is to expand this equation and put it in the form
ax^2+bx+c. Firstly, multiply the first two binomials (in the parentheses):


= 4x(x+9)-2(x+9)-3x\\= 4x^2+36x-2(x+9)-3x\\= 4x^2+36x-2x-18-3x

Now, we can combine like terms (terms with like variables):


= 4x^2+36x-2x-3x-18\\= 4x^2+31x-18

Now, in this equation, we can easily identify that 31 is the value of b in
ax^2+bx+c.

I hope this helps!

User Lepture
by
5.3k points